Protection of Offshore Critical Energy Infrastructure Beyond National Sovereignty: Military Rules of Engagement and Barriers - Andrei, Roxana (2025)
Europe has been experiencing, particularly after February 2022, the emergence and the proliferation of new fastevolving security risks, threats and vulnerabilities to the OCEI in all four major maritime regions of the EU (the North Sea-Atlantic region, the Baltic Sea, the Black Sea and the Mediterranean Sea). In these maritime regions, disputes over rights to exploit offshore natural resources like natural gas are common. Since 2022, there has been a rise in military activity, including contested zones and mine placements, threatening offshore exploration safety. Additionally, offshore infrastructures face cybersecurity threats and hybrid warfare tactics. Thus, the study outlines current threats, risks, and vulnerabilities to the safety of EU Offshore Critical Energy Infrastructure (OCEI) in both conventional and hybrid scenarios.